DATA ACQUISITION IN RUNNING TRIPLE COMBO, A COMBINATION OF MEASUREMENT WHILE DRILLING (MWD) AND LOGGING WHILE DRILLING (LWD) WITH NUCLEAR LOGGING TOOL, ASSESSED BY SAFETY ASPECTS - Lilis Susanti Setianingsih (Jurusan Teknik Informatika, 2010)
Drilling and exploration in oil and gas jobs require accurate yet fast data on formation being drilled. This type of activity utilizes services providing real time logs with triple combo combining MWD (Measurement While Drilling) and LWD (Logging While Drilling). The advanced technology of LWD and MWD lets the operator companies reach quick and precise decision regarding the drilling and exploration activities based on formation evaluation which can be presented in real time. Nuclear logging which can be included in a MWD and LWD triple combo presents formation evaluation through density and porosity logs. The technique adapted for the nuclear logging is by implementing density measurements by using Cs-137 gamma ray source while porosity measurements are obtained by using fast neutrons from americium oxyde-berryllium (AmBe). Data acquisition for real time data presentation is performed by attaching two pressure sensors and one depth sensor at the surface. As the triple combo is run with the whole three tools for MWD, Resistivity tool for getting resistivity logs and the nuclear logging tool to be put on the top of the formation, the sequence of procedures to follow are strictly specific. Requirement for safety to be concerned in LWD application with radioactive source is regulated by BAPETEN. Government Regulation No. 33/2007 about Safety for Ionizing Radiation and Security for Radioactive Source as well as Government Regulation No 29/2008 about Licensing for Utilization of Ionizing Radiation Source and Nuclear Material. The types of the well require concerns regarding the type of formation that can affect the risk in running the job. Based on the safety assessment done on practice in the field, most activities have complied with the existing regulation.